Expanding the Phenotypic Spectrum of PRKD1 Gain-of-Function Syndrome: Congenital Heart Disease, Bilateral Carotid Dissections, and Ectodermal Dysplasia in an Adult Patient - Pedram Kharaziha; Klara Junker; Josefine Åhsberg; Antheia Kissopoulou (Genes, 2026)
Background: PRKD1-related congenital heart defects and ectodermal dysplasia syndrome (CHDED) is a rare multisystem developmental disorder caused by heterozygous gain-of-function variants in PRKD1. Reported phenotypes include congenital heart defects, ectodermal abnormalities, limb anomalies, and neurodevelopmental impairment, while vascular manifestations remain poorly characterized. We report an adult patient with a de novo PRKD1 variant and bilateral carotid artery dissections. Methods: Clinical, cardiovascular, neurological, and genetic evaluations were performed, including SNP-microarray and trio whole-exome sequencing with additional analysis of genes associated with heritable thoracic aortic and connective tissue disorders. Results: The patient was diagnosed at 35 years of age with a de novo PRKD1 c.1808G>A p.(Arg603His) variant. He had childhood-onset congenital heart disease, ectodermal and skeletal abnormalities, hearing impairment, infertility, and learning difficulties. In adulthood, he developed bilateral carotid artery dissections and mild aortic dilatation. No additional pathogenic or likely pathogenic variants were identified in the evaluated connective tissue and heritable aortic disease genes. The PRKD1 variant was absent or extremely rare in population databases and had supporting functional evidence for a gain-of-function effect. Conclusions: This case raises the possibility of a previously unrecognized vascular manifestation of PRKD1-related CHDED. Although a biological association is plausible, causality cannot be established from a single case. Further clinical and functional studies are needed to determine whether vascular fragility is a recurrent feature of PRKD1-related disease. This case also highlights the importance of considering rare genetic syndromes in patients with unexplained arteriopathy and congenital heart disease.